(3GdGOGQI GdeGdjIs - (3Ydj(B, (3YHGSs ((3YeGf(B:s (3OGQ GKQGA ddfTQ(B,s, 2008)
(3jYQV gPG GdcJGH WHjYI h eLGd GdGOGQI GdeGdjI(B/(3GdbhGFe GdeGdjI(B/(3GdJMdjd GdeGdj(B/(3GdbjeI GdRefjI ddfbhO(B/(3GdeNGWQ h eYOd GdYGFO(B/(3cdaI QGS GdeGd(B/(3Jbjje GdGSJKeGQGJ GdQCSeGdjI(B/(3GdQaY GdeGdj h fbWIGdJYGOd(B/(3GdJehjd(B/(3EOGQI QCS GdeGd GdYGed(B/(3EOGQI GdfbOjI(B/(3EOGQI GdPee GdeOjfI(B/(3EOGQI GdeNRhf GdSdYj(B. s
Keywords: (3GOGQI eGdjIs; (3JMdjd eGdjs